HIV in acute care: a review of the burden of HIV-associated presentations to an Emergency Department - B. Naicker; R. C. Maharaj (South African Family Practice)
Objective: To determine the burden of human immunodeficiency virus (HIV) disease and co-infection on a district-level Emergency Department (ED) in KwaZulu-Natal.